Cytidine deaminase enzymatic activity is a prognostic biomarker in gemcitabine/platinum-treated advanced non-small-cell lung cancer: a prospective validation study. Issue 11 (27th November 2018) - Tibaldi, Carmelo; Camerini, Andrea; Tiseo, Marcello; Mazzoni, Francesca; Barbieri, Fausto; Vittimberga, Isabella; Brighenti, Matteo; Boni, Luca; Baldini, Editta; Gilli, Annalisa; Honeywell, Richard; Chartoire, Myriam; et al.
Abstract Background Cytidine deaminase (CDA) plays a crucial role in the degradation of gemcitabine. In our previous retrospective study, CDA enzymatic activity was the strongest prognostic biomarker of the activity and efficacy of platinum/gemcitabine combinations. The aim of this prospective study was to validate the prognostic role of CDA activity in the first-line treatment of advanced non-small-cell lung cancer. Methods A total of 124 untreated patients received standard doses of platinum/gemcitabine. CDA activity was baseline measured in plasma samples by spectrophotometric assay. Results Using the median CDA level as cut-off, in the patients with high versus low CDA activity the response rate was 25.0% (95% CI, 14.7–37.8) and 54.1% (95% CI, 40.8–66.9), P = 0.0013; the 6-month progression rate was 34.5% (95% CI, 22.6–46.6) and 54.1% (95% CI, 40.9–65.6), HR = 2.01 (95% CI, 1.32–3.06), P < 0.001; the 1-year survival rate was 23.3% (95% CI, 13.6–34.6) and 57.3% (95% CI, 43.9–68.6), HR = 2.20 (95% CI, 1.46–3.34), P = 0.0002, respectively. CDA activity resulted to be an independent prognostic factor for progression and survival at multivariate analysis. Conclusions This study validated prospectively the prognostic role of the CDA activity and should prompt larger and adequately designed randomised prospective studies to establish the predictive impact of this test in improving the outcome of selected patients.